Introduction of the Transregional Collaborative Research Center TR 172: Arctic Amplification - Wendisch, Manfred; Brückner, Marlen; Burrows, John P.; Crewell, Susanne; Dethloff, Klaus; Ebell, Kerstin; Lüpkes, Christof; Macke, Andreas; Notholt, Justus; Quaas, Johannes; Rinke, Annette; Tegen, Ina (Universität Leipzig, 2017)
A new German research consortium is investigating the causes and effects of the rapid rise of near-surface air temperatures in the Artic. Within the last 25 years a remarkable increase of the Arctic near-surface air temperature exceeding the global warming by a factor of two to three has been observed. The phenomenon is commonly referred to as Arctic Amplification. The warming results in rather drastic changes of a variety of climate parameters. For example, the Arctic sea ice has declined significantly. This ice retreat has been well identified by satellite measurements. However, coupled regional and global climate models still fail to reproduce it adequately; they tend to systematically underestimate the observed sea ice decline. This model observation difference implies that the underlying physical processes and feedback mechanisms are not appropriately represented in Arctic climate models. Thus, the predictions of these models are also likely to be inadequate. It is mandatory to identify the origin of this disagreement. Ein neu geschaffenes deutsches Forschungskonsortium untersucht die Ursachen und Effekte des rapiden Anstiegs der bodennahen Lufttemperatur in der Arktis. Innerhalb der letzten 25 Jahre wurde ein bemerkenswerter Anstieg der Bodenlufttemperatur in der Arktis beobachtet, welcher die globale Erwärmung um den Faktor 2 bis 3 übersteigt. Dieses Phänomen wird als arktische Verstärkung bezeichnet. Diese Erwärmung resultiert vielmehr in einer drastischen Änderung einer Vielzahl von Klimarparametern. Beispielsweise ist das arktische Meereis deutlich zurückgegangen. Dieser Eisrückgang wurde durch Satellitenbeobachtungen gut beobachtet. Dagegen haben regionale und globale Klimamodelle immer noch Probleme, den Rückgang entsprechend zu reproduzieren. Sie tendieren dazu, den Meereisrückgang systematisch zu unterschätzen. Die Unterschiede zwischen Modell und Beobachtungen legen nahe, dass die grundlegenden physikalischen Prozesse und Rückkopplungsmechanismen nicht entsprechend in arktischen Klimamodellen ...